Pengaruh Media YouTube terhadap Hasil Belajar IPA Materi Tekanan Siswa SMPN 1 Polongbangkeng Utara - Yusfhika Rezky Amelya; Putri; Edy Kurniawan; Asyriani Ishak (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyse the effect of using YouTube on science learning outcomes in pressure-related material for students at SMPN 1 Polongbangkeng Utara. The background to this study is based on students' difficulties in understanding the abstract concept of pressure, which requires visualisation to reinforce understanding. The research approach used is descriptive quantitative with a quasi-experimental design through the administration of pre-tests and post-tests to 20 students. The results of the study show an increase in the average score from 64.5 on the pretest to 83.5 on the posttest, accompanied by a decrease in standard deviation from 24.95 to 17.11. These findings indicate that YouTube is effective in improving students' understanding of concepts and equalising learning outcomes. This effectiveness is in line with multimedia learning theory, which emphasises the importance of combining visual and audio elements in the learning process. Thus, YouTube can be used as an alternative learning medium that can improve science learning outcomes, particularly in pressure-related material.